The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/0102-77863630101
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação dos Modelos de Interação Atmosférica e de Incêndio Florestal BRAMS-SFIRE no sul de Portugal

Abstract: Resumo O BRAMS-SFIRE é um novo sistema de modelação atmosférica com componente de propagação de fogo desenvolvido no Centro de Previsão de Tempo e Estudos Climáticos (CPTEC / INPE) no Brasil em colaboração com o Instituto Mediterrâneo de Agricultura, Ambiente e Desenvolvimento (MED) em Portugal. O presente artigo descreve a incorporação do modelo de propagação de fogo no Brazilian developments on the Regional Atmospheric Modeling System (BRAMS). Os principais objetivos foram desenvolver o acoplamento entre um … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The SFIRE model (Mandel et al, 2009(Mandel et al, , 2011 coupled to BRAMS (Freitas et al, 2017) by Menezes (2016Menezes ( , 2021a allows the analysis of surface fire behaviour taking into account the type of fuel bed and its moisture, the topography and the atmospheric wind. Under the FIRESMOKE project, the developments of BRAMS-SFIRE comprise the up-grade for the last version of SFIRE, the introduction of a mathematical model for predicting surface fire spread (Rothermel, 1972) for fire behaviour fuel model 10 (timber litter and understory) (Anderson, 1982) and of the conceptual model for predicting behaviour and size of crown fires from Rothermel (1991), including conditions for the crown fire starting and spreading for coniferous forest fuel types (Van Wagner, 1977), based on the research of Scott and Reinhardt (2001).…”
Section: Overview Of Ongoing Fire Developments On Bramsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SFIRE model (Mandel et al, 2009(Mandel et al, , 2011 coupled to BRAMS (Freitas et al, 2017) by Menezes (2016Menezes ( , 2021a allows the analysis of surface fire behaviour taking into account the type of fuel bed and its moisture, the topography and the atmospheric wind. Under the FIRESMOKE project, the developments of BRAMS-SFIRE comprise the up-grade for the last version of SFIRE, the introduction of a mathematical model for predicting surface fire spread (Rothermel, 1972) for fire behaviour fuel model 10 (timber litter and understory) (Anderson, 1982) and of the conceptual model for predicting behaviour and size of crown fires from Rothermel (1991), including conditions for the crown fire starting and spreading for coniferous forest fuel types (Van Wagner, 1977), based on the research of Scott and Reinhardt (2001).…”
Section: Overview Of Ongoing Fire Developments On Bramsmentioning
confidence: 99%
“…The BRAMS-SFIRE system (Menezes et al, 2016(Menezes et al, , 2021aFreitas et al, 2017) aims at overcoming this challenge. BRAMS is continuously under development to better simulate atmospheric processes and the coupled SFIRE simultaneously simulates the interactions between the surface fire fluxes and the atmospheric environment, both on the mesoscale and micro-scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) Quantities Q j and P i are intimately related to the study of terrain properties (an example can be found in the work [8]). In the absence of an external vectorial influence, such as wind or slope, which directly affects fire trajectory, ψ ij = 0 and therefore, ψ ij is not considered for the calculation of p ij .…”
Section: Homogeneous Gridmentioning
confidence: 99%
“…Fire behaves according to three interacting physical factors: fuel availability (morphological and physiological characteristics of vegetation), weather (wind speed and direction, temperature, and relative humidity) and terrain (slope and aspect) [7,8]-along this article we will refer to such factors as FWT conditions. Based on the knowledge of a land patch regarding these factors, and data on the initial fire condition it's possible to calculate an average value for the fire spreading rate [9].…”
Section: Introductionmentioning
confidence: 99%